Descent of Fetal Head into The Pelvic Inlet in Primigravida: Systematic Review - Sihotang, Imanuel; Sitepu, Makmur; Rusda, Muhammad (Talenta Publisher, 2021)
Background: Skilled care before, during and after delivery can save the lives of women and newborns. Antenatal care is useful for detecting problems in pregnancy and childbirth, as well as preparing for labor. It is estimated that labor will begin 2-3 weeks after the entry of the fetal head on pelvic inlet. Objective: This study was conducted to determine the prevalence of descending of the fetal head at the pelvic inlet in the primigravida of 34-36 weeks of gestation. Methods: This study uses a systematic review study method with the data used are the results of research that have been circulating in the world. Results: In Weekes and Flynn's (1975) study, the entry of the fetal head into the pelvic cavity and having passed the pelvic inlet with a sample of 422 primigravidas, the prevalence was 34 weeks (2%), 35 weeks (1%). Of the three studies analyzed at 36 weeks' gestation, a prevalence was 4.22%.